Commissioning and Operation of the AG Mills at the Aitik Expansion Project (aaf8f334-a1ef-48c8-b4f0-2d5b88480a9a) - S. Markstrom (Canadian Institute of Mining, Metallurgy and Petroleum, 2012)
The Boliden AITIK copper mine is located 100 kilometres north of the Arctic Circle in northern Sweden. A pre-feasibility study was conducted in 2005 with the aim of increasing the capacity of the existing processing plant. After analysis, options to upgrade the existing plant were abandoned in favour of building a new processing plant, with higher capacity and therefore greater profitability. A new plant could be designed with greater flexibility to make potential future expansions easier. A feasibility study for a new 36 Mt/y processing plant including fully AG grinding circuits and flotation was completed in 2006. The project was approved by the Boliden board shortly thereafter. Construction started in the beginning of 2007 and was completed during 2009. Commissioning of the new plant was undertaken in the first half of 2010. The grinding circuit consists of two lines with each line consisting of a 22.5 MW AG mill and a 10 MW Pebble mill in closed circuit with a spiral classifier. The nominal production level is 2 200 t/h for each grinding line. This paper presents the start-up and operation of the grinding circuit.